The Influence Of Teaching Communication Strategies On Tertiary Iraqi EFL Students’ Fluency And Self-Confidence - Al-Geburi, Raed Latif Ugla (2018)
This study examines the influence of communication strategy instruction on tertiary Iraqi EFL students’ fluency and self-confidence. For the purpose of this study, 50 tertiary Iraqi EFL students were selected and divided into three proficiency levels (low, intermediate, high). In this study, the researcher used quasi experimental one group pretest-posttest design. All the students received 10-week communication strategies training lessons. These lessons were based on teaching 10 kinds of communication strategies which were selected from taxonomies of Dörnyei and Scotts’ (1995a, 1995b) and Farrahi's (2011).